Fiscal Balance During Inflation, Disinflation, and Immigration : Policy Lessons - Razin, Assaf (IMF Working Papers; Working Paper, 1996)
The paper provides an overview of the role of the fiscal imbalances and the ensuing public debt in explaining major episodes in Israel's recent economic developments. The main conclusions from the Israeli budgetary developments may have more general validity: (a) deficits lead to inflation and stopping inflation requires elimination of deficits; (b) a major effect of inflation is a large shift of the tax burden from capital to labor; and (c) shocks to labor supply, such as massive labor inflow through immigration, can be absorbed without worsening government finances, when the labor and the housing markets are sufficiently flexible.